2022
DOI: 10.3390/ijms231911542
|View full text |Cite
|
Sign up to set email alerts
|

Probing Mechanisms of Binding and Allostery in the SARS-CoV-2 Spike Omicron Variant Complexes with the Host Receptor: Revealing Functional Roles of the Binding Hotspots in Mediating Epistatic Effects and Communication with Allosteric Pockets

Abstract: In this study, we performed all-atom MD simulations of RBD–ACE2 complexes for BA.1, BA.1.1, BA.2, and BA.3 Omicron subvariants, conducted a systematic mutational scanning of the RBD–ACE2 binding interfaces and analysis of electrostatic effects. The binding free energy computations of the Omicron RBD–ACE2 complexes and comprehensive examination of the electrostatic interactions quantify the driving forces of binding and provide new insights into energetic mechanisms underlying evolutionary differences between O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 139 publications
6
24
0
Order By: Relevance
“…Interestingly, these positions are distributed across both major patches of the binding interface. This analysis is also consistent with our previous studies, suggesting that these conserved hydrophobic RBD residues may be universally important for binding across all Omicron variants and act as stabilizing sites of the RBD stability and binding affinity [86,87]. The common energetic hotspots Y453, F456, Y489 and Y501 found in the computational mutational scanning also emerged as critical stability and binding hotspots in the DMS studies [58,59].…”
Section: Computational Mutational Scanning Of the Rbd Residues Identi...supporting
confidence: 90%
“…Interestingly, these positions are distributed across both major patches of the binding interface. This analysis is also consistent with our previous studies, suggesting that these conserved hydrophobic RBD residues may be universally important for binding across all Omicron variants and act as stabilizing sites of the RBD stability and binding affinity [86,87]. The common energetic hotspots Y453, F456, Y489 and Y501 found in the computational mutational scanning also emerged as critical stability and binding hotspots in the DMS studies [58,59].…”
Section: Computational Mutational Scanning Of the Rbd Residues Identi...supporting
confidence: 90%
“…150 A network-based adaptation of the reversed allosteric communication approach was proposed to identify allosteric hotspots and infer this analysis to characterize the distribution of allosteric binding pockets (Figure 3) in the SARS-CoV-2 Spike Omicron BA.1, BA.1.1, BA.2, and BA.3 variant complexes. 151 Integrative computational and experimental studies detailed allosteric communications in an S protein trimer and validated the allosteric site located between SD1 and SD2 subdomains of the S protein (Figure 3). 152 By screening commercial compound databases, several hits were selected and validated at both the molecular level and cellular level for their binding strength and antivirus activities (Figure 4).…”
Section: ■ Allosteric Regulation Models and Machine Learning In Struc...mentioning
confidence: 85%
“…The functional and systems biology studies reinforced the notion that the Omicron mutations may have emerged as an evolutionary product of balancing multiple fitness requirements, including the immune escape, productive binding with the host receptor, conformational plasticity, and allosteric communications. , The reversed allosteric communication approach is based on the premise that allosteric signaling in proteins is bidirectional and can propagate from an allosteric to orthosteric site and vice versa, thus providing means for detecting cryptic allosteric sites. , An integrated computational and experimental strategy exploited the reversed allosteric communication concepts to combine MD simulations with MSM for characterization of binding shifts in the protein ensembles and identification of cryptic allosteric sites . A network-based adaptation of the reversed allosteric communication approach was proposed to identify allosteric hotspots and infer this analysis to characterize the distribution of allosteric binding pockets (Figure ) in the SARS-CoV-2 Spike Omicron BA.1, BA.1.1, BA.2, and BA.3 variant complexes . Integrative computational and experimental studies detailed allosteric communications in an S protein trimer and validated the allosteric site located between SD1 and SD2 subdomains of the S protein (Figure ).…”
Section: Allosteric Regulation Models and Machine Learning In Structu...mentioning
confidence: 99%
“…It was also suggested that the SARS-CoV-2 S protein may exploit the plasticity of the RBD to generate escape mutants while engaging a small group of functional hotspots to mediate efficient local binding interactions and long-range allosteric communications with ACE2 [ 76 ]. All-atom MD simulations of the RBD-ACE2 complexes for BA.1 BA.1.1, BA.2, and BA.3 Omicron subvariants were combined with a systematic mutational scanning of the RBD-ACE2 binding interfaces, revealing functional roles of the key Omicron mutational sites R493, R498, and Y501 acting as binding energy hotspots, drivers of electrostatic interactions, and mediators of epistatic effects and long-range communications [ 77 ].…”
Section: Introductionmentioning
confidence: 99%